2014
DOI: 10.1007/s10499-014-9810-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of genetics factor on key growth traits and quantitative genetic analysis of sea cucumber Apostichopus Japonicus (Selenka) heat-resistant and fast-growing strain

Abstract: Using incomplete diallels cross and North Carolina II design, this study established sea cucumber families with heat-resistant and fast-growing Apostichopus japonicus strains from different ecological areas. Then, this study analyzed the influence of paternal and maternal genetic effects on the growth of A. japonicus, evaluated the growth effect of different A. japonicus families in the early growth stage and estimated the combining ability and heritability. The study showed that, in the early growth stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Unsynchronous growth has always been a challenge in the rearing of aquatic animals [ 14 ]; it may cause a lot of problems, such as inconvenient management, longer farming cycles and the decrease in commercial value due to uneven sizes [ 15 ]. Previous studies have revealed that growth is a complex process, involving multiple regulatory effects of a large number of genes and metabolites [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unsynchronous growth has always been a challenge in the rearing of aquatic animals [ 14 ]; it may cause a lot of problems, such as inconvenient management, longer farming cycles and the decrease in commercial value due to uneven sizes [ 15 ]. Previous studies have revealed that growth is a complex process, involving multiple regulatory effects of a large number of genes and metabolites [ 16 ].…”
Section: Introductionmentioning
confidence: 99%